Role of Serum Magnesium Deficiency in Insulin Resistance Among Overweight and Obese Children - Sapna Sindhu, Surhan, Asadullah, Hina Umair, Qamar Yasmeen, Razwan Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Childhood obesity has become a major public health concern in Pakistan, contributing to early-onset insulin resistance and increased risk of type 2 diabetes mellitus. Micronutrient deficiencies, particularly magnesium deficiency, are increasingly recognized as contributors to impaired glucose metabolism. Magnesium is a key intracellular cation that plays a critical role in insulin receptor activation, glucose transport, and enzymatic reactions regulating carbohydrate metabolism. However, limited data exist on the prevalence of magnesium deficiency and its relationship with insulin resistance in overweight and obese children in South Asia. Objectives: The aim of this study was to determine the prevalence of serum magnesium deficiency and to evaluate its association with insulin resistance among overweight and obese children in Pakistan. Methods: A cross-sectional study was conducted in the Department of Pediatrics, Unit II, Liaquat University Hospital, Hyderabad/Jamshoro, Pakistan, from January 2022 to March 2023. A total of 120 children aged 6–16 years with BMI ≥85th percentile were enrolled. Anthropometric measurements were taken, and fasting blood samples were collected for serum magnesium, glucose, and insulin estimation. Insulin resistance was calculated using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), defined as fasting insulin in micro–international units per milliliter multiplied by fasting glucose in milligrams per deciliter, divided by four hundred and five. A value greater than 3.16 was considered diagnostic of insulin resistance. Results: The prevalence of magnesium deficiency was 43.3%. Children with magnesium deficiency had significantly higher fasting insulin levels (18.6 ± 5.2 vs. 12.4 ± 3.8 μIU/mL, p < 0.001) and HOMA-IR scores (4.8 ± 1.5 vs. 3.1 ± 1.0, p < 0.001) compared to those with normal magnesium status. Multivariate regression confirmed low magnesium as an independent predictor of insulin resistance after adjusting for age, sex, and BMI (β = -0.35, p = 0.002). Conclusion: Serum magnesium deficiency is common among overweight and obese children in Pakistan and is strongly associated with insulin resistance. Routine screening and nutritional interventions targeting magnesium intake may help reduce metabolic risk in this vulnerable population. Keywords: Magnesium deficiency, insulin resistance, obesity, overweight, children, HOMA-IR